“Unusual, Unstable, Complicated, Unreliable and Temporary” Reinterpreting the ebb and flow of globalization - Bordo, MD; Schenk, C (Hoover Institution, 2019)
In 1919, John Maynard Keynes wrote his famous tract, The Economic Consequences of the Peace. In that work he anticipated the collapse of the first era of globalization that began in the mid nineteenth century. He admonished the short-sighted assumption that these years of relative peace and prosperity for many was a permanent norm, interrupted only briefly by the Great War. The diplomatic failures, lapses in leadership and promotion of narrow interests and vision outlined by Keynes underpinned his prediction of a backlash of economic nationalism, trade protectionism and recession. The paper revisits the turning points in the evolution of the global economic system since 1919 by focusing primarily on the evolution of the international monetary system and policy cooperation/coordination. We identify four disruptions and examine how each prompted change in the underlying ideology about how the international monetary system should be organized: World War I, Bretton Woods, the Managed Float, and the 2007-2008 global financial crisis. Each turning point was characterized by different forms and institutions of cooperation, how rules (either explicit or implicit) were designed and implemented, and the crucial importance of the historical context.